(3GdJGQjN GdcHjQs - (3eMeO Hf ESeGYjd Hf EHQGgje GdLYaj GdHNGQj, CHh YHO Gddg , J (B256 (3g` s; (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s
(3ChdgG (B:s
(3jHOC HbjI JQGLhe ef ESeg GHQGgje , hChd eGajg EHQGgje Hf eMeO CHhYHOGddg GdfNdj s
(3BNQgG (B:s
(3jfJgi HBNQ JQGLe ef CSeg BOe aj JQLeI BOe Hf GdRHQbGf s
(3GfXQ Qbe (B123s
(3Qbe (B961 (3JGQjNs
(3fSNI KGdKI GdehLhO efg GdLRA GdKGdKs
(3hgPG GdLRA HQhGjI CHj HcQ CMeO Hf YHOGf Hf eMeO GdMGaX GdTjQGRj s
(3hCHj CMeO YHOGdhgGH Hf eMeO Hf ehSi GdZfONGfj s
(3hYdjg SeGYGJ eNJdaI s
Keywords: (3GdJGQjNs